Pengaruh Kompetensi Pedagogik serta Kreativitas Guru pada Prestasi Belajar Murid pada Mata Pelajaran Pendidikan Kewarganegaraan : The Influence of Pedagogical Competence and Teacher Creativity on Student Learning Achievement in Civic Education Subjects - Yuli Oslin Imelda Br. Purba; Wesly Nababan; Sabar Dumayanti Sihombing (ITScience (Information Technology and Science), 2025)
This research aims to determine the influence of pedagogical competence on students' learning achievement in Civics Education of Grade XI of State Senior High School 3 Pematangsiantar. To determine the influence of teacher creativity on students' learning achievement in Civics Education of Grade XI of State Senior High School 3 Pematangsiantar. To determine the influence of pedagogical competence and teacher creativity on students' learning achievement in Civics Education of Grade XI of State Senior High School 3 Pematangsiantar. This research method applies a quantitative research method with an ex post facto approach. This research was implemented in State Senior High School 3, Pematangsiantar. The sampling technique chosen by the researcher is the probability sampling technique. This method does not apply a fixed or standard selection process; when applying this technique, not all populations have the same opportunity to be sampled. The sample in this research is all grade XI students at SMA Negeri 3 Pematangsiantar, which consists of 4 classes with 144 students. The research results show that the sig score is 0.007, the calculated t score is 2.366 on the X1 variable, and the sig score is 0.003 on the X2 variable. The sig score is 0.000, the calculated f score is 3.661, the table f score is 3.17, and the sig level score is 0.05. Conclusion H1 in the first hypothesis is accepted, namely, Pedagogical Competence and Teacher Creativity have a separate effect on Learning Achievement. H1 in the third hypothesis is accepted: pedagogical competence and teacher creativity have a joint effect on learning achievement performance.